Effectiveness of Virtual Reality-Based Interventions for Children and Adolescents with ADHD: A Systematic Review and Meta-Analysis - Dulce Romero-Ayuso; Abel Toledano-González; María del Carmen Rodríguez-Martínez; Palma Arroyo-Castillo; José Matías Triviño-Juárez; Pascual González; Patrocinio Ariza-Vega; Antonio Del Pino González; Antonio Segura-Fragoso (MDPI AG, 2021)
This review aims to evaluate the effectiveness of virtual reality-based interventions (VR-based interventions) on cognitive deficits in children with attention deficit hyperactivity disorder (ADHD). A systematic review and meta-analysis were performed according to the PRISMA statement and the Cochrane Handbook guidelines for conducting meta-analyses. The Grading of Recommendations, Assessment, Development and Evaluation (GRADE) was used to assess the quality of the evidence. Clinical trials published up to 29 October 2020, were included. The meta-analysis included four studies, with a population of 125 participants with ADHD. The magnitude of the effect was large for omissions (SMD = −1.38; p = 0.009), correct hits (SMD = −1.50; p = 0.004), and perceptual sensitivity (SMD = −1.07; p = 0.01); and moderate for commissions (SMD = −0.62; p = 0.002) and reaction time (SMD = −0.67; p = 0.03). The use of VR-based interventions for cognitive rehabilitation in children with ADHD is limited. The results showed that VR-based interventions are more effective in improving sustained attention. Improvements were observed in attentional vigilance measures, increasing the number of correct responses and decreasing the number of errors of omission. No improvements were observed in impulsivity responses.